2021
DOI: 10.51341/1984-3925_2021v24n1a1
|View full text |Cite
|
Sign up to set email alerts
|

Evidenciação do Contexto Econômico na Relação entre Governança Corporativa e Volatilidade das Ações nas Companhias Abertas Brasileiras

Abstract: Objective: to analyze how the economic context affects the relationship between corporate governance and stock market volatility of Brazilian public companies listed on B3 S.A. - Brasil, Bolsa, Balcão (B3), from 2010 to 2018.Method: based on quantitative, descriptive, and documentary research, the stock market volatility on an annual basis was used as a metric for volatility (dependent variable); internal mechanisms (ownership and control structure, number of members of the administrative and fiscal council) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Also in Jordan, Alawin (2014) investigated the impact of ownership structure measured in terms of the percentage of ownership by top owners, percentage of ownership by foreigners, percentage of ownership by individuals, and percentage of ownership by institutions on stock price volatility for firms listed in the Amman stock exchange, where it was found that the percentage of ownership by top owners showed a significant positive impact on volatility. Machado et al (2021) examined the impact of internal and external CG mechanisms on stock market volatility in Brazil, in addition to the moderating impact of GDP on the relationship between CG mechanisms and stock market volatility for companies listed on B3 SA Brasil Bolsa Balcao. The internal CG mechanisms included ownership and control structure, as well as the number of members of the administrative and fiscal council.…”
Section: Corporate Governance and Stock Price Volatilitymentioning
confidence: 99%
“…Also in Jordan, Alawin (2014) investigated the impact of ownership structure measured in terms of the percentage of ownership by top owners, percentage of ownership by foreigners, percentage of ownership by individuals, and percentage of ownership by institutions on stock price volatility for firms listed in the Amman stock exchange, where it was found that the percentage of ownership by top owners showed a significant positive impact on volatility. Machado et al (2021) examined the impact of internal and external CG mechanisms on stock market volatility in Brazil, in addition to the moderating impact of GDP on the relationship between CG mechanisms and stock market volatility for companies listed on B3 SA Brasil Bolsa Balcao. The internal CG mechanisms included ownership and control structure, as well as the number of members of the administrative and fiscal council.…”
Section: Corporate Governance and Stock Price Volatilitymentioning
confidence: 99%